From indigenous screening to pilot fermentation: comprehensive characterization of Bacillus subtilis YZ01 as a novel food-grade probiotic candidate - Cao, Xiaoyu; Zhang, Yu; Xu, Qianqian; Yan, Hai (Frontiers in Microbiology, 2025)
Bacillus subtilis YZ01, a novel strain isolated from the feces of a healthy individual, demonstrated potent in vitro biodegradation of uric acid (54.13%) and nucleosides (41.21%). Phylogenomic analysis of 2,198 single-copy orthologous genes confirmed strain YZ01’s taxonomic identity, while genome mining uncovered five circular antimicrobial peptide clusters. B. subtilis has been extensively utilized in the food industry for decades and is on the U.S. Food and Drug Administration’s GRAS (Generally Recognized as Safe) list. Integrated genomic and phenotypic characterization revealed the probiotic properties and safety profile of B. subtilis YZ01, and proposed pathways for its biodegradation of uric acid and nucleosides. In vitro assays indicated that B. subtilis YZ01 exhibits excellent acid and bile salt tolerance as well as good adhesion, supported by the presence of stress-response genes, adhesion-associated surface proteins, and bile salt hydrolase genes. Antibiotic resistance genes and virulence factors were identified and confirmed to be safe through associated tests (antibiotic resistance, hemolytic assay, cytotoxicity assay and biogenic amine production). Furthermore, pilot-scale fermentation in a 100 L fermenter achieved high-density biomass production (6.12 × 1010 CFU/mL) under optimized culture conditions, underscoring its industrial scalability. These findings highlight B. subtilis YZ01’s bioactive properties, food-safe profile, industrial feasibility, and promising potential as a probiotic candidate for the development of functional foods aimed at improving hyperuricemia.